Storage of sunflower-seeds: Variation on the wax content of the oil - Martini, Silvana (2005)
Storage conditions of oil seeds before industrial extraction might influence the quality of the crude oil. The objective of this work was to study the influence of sunflower seed storage conditions (temperature and time) on the quality of the resulting oil in terms of its wax content and composition. Sunflower seeds were stored under different conditions, 10, 21 and 37°C, in sealed recipients. Extractions of the seeds with hexane were made to obtain the oil at different storage times. The amount of oil extracted (25-40%) showed no significant differences with storage conditions. Wax content of the samples was determined with two different methods (laser polarized turbidimetry and microscopy), and results showed that wax concentration increased with storage conditions (time and temperature). Composition of wax components, determined using capillary gas chromatography, during storage was approximately constant for C35-C39 and showed significant differences for C 40-C48 components. Waxes with high carbon number cause more turbidity than waxes with low carbon number, due to their higher melting point, resulting in a low-quality crude oil and therefore in variations in processing conditions during the oil refining. According to the data showed in this study, seed storage at low temperatures during short periods of time may be the more adequate conditions to obtain high-quality oil.